Museernes Fremtid - Kjærgaard, Thorkild (Kuml, 2001)
The future of the museums A lot of people worry on behalf of the museums. Museums are boring and dusty, and no one can be bothered to visit them, the young ones not at all, they want adventure, they want int eractive computer games. In a report published jointly by Elsebeth Gerner Nielsen, minister of cultural affairs, and Pia Gjellerup, then minister of commerce, in December 2000, the two ministers decreed that ”it is necessary for Danish economy that the cultural sector – museums, too – begin to think commercially.” If one asks what it takes, the answer is often: ”make the museum s come alive.” A visit to a museum should be an experience similar to a visit to Legoland or Disneyland. We presently see museum leaders anxious about being left behind by the development and feverishly trying to make their museums come alive. Visitors’ centres spring up like mushrooms in the Danish museum landscape, and the National Museum in Copenhagen recently hosted the Missing Link – alive! exhibition, which illustrated the development of humankind through four million years. Here, showcases contained moving robots, interactive elements where the visitors could measure their strength against the Neanderthal Man, compare hands with some of our supposed ancestors, touch copies of tools, answer questions about the development of man etc. – hardly any original material was presented. It is my belief that the idea shared by politicians and some museums – that re-enactment may attract visitors – is utterly unrealistic and that too much attention is paid to a couple of isolated successes. l am not against people having a good time. However, I do not think this an area for the museums to make themselves seriously felt. Other media deal with history coming alive. Historical plays by Shakespeare, Racine, Johann Friedrich Schiller and August Strindberg have been performed a thousand times. People have cried in torrents over the destiny of Anne Frank, they have shivered to witness the brutal murder on Julius Caesar, and they have breathlessly followed the conflict between Charles V and his son, Don Carlos, the governor of the Netherlands, which is described by Schiller in such a spellbinding fashion. Museums will never be able to create anything similar to this, no matter how much they dress the ticket seller or the museum keepers in medieval clothing, and no matter how many monkey tricks are made in the museum cafés in order to serve medieval food and sour ale. Re-enacting the past is not a museum task. Films, theatre, and literature will do that. Still, this does not mean that there is no room for museums. Because the museums have something no one else has. They have things from the past. Most things by far are lost in the course of time, and so it should be. At least that is how it is. Most furniture is worn out and goes to pieces, and the same fate befalls clothes, glasses, shoes, cars, toys, tractors, packing, calculating machines, ladles, anything. Things are perishable; they disappear due to the ravages of time. Items slip away between our hands, just as the time, and much faster than we think. In most homes only a few things are older than fifty years. So, the museums are treasuries that protect the few remaining items for eternity. Only a single pale yellow wrong-coloured Swedish three-shilling stamp from 1855 exists. It is the world’s most expensive stamp, traded in the 1990s for thirty million Dkr. It is depicted in books on stamps, you see it in newspapers, on the Internet, everywhere, but there is only a single original one. It was sold for a fortune, the rest of the millions of reproductions of it have no price – they are used for wrapping up fish, they are me rely copies. The whole truth, the whole authenticity, the radical certainty that in 1855, a Swedish printer by mistake used a three-shilling pr inting plate while printing yellow eightshilling stamps is held within the pushing presence of the original. The aura of authenticity raises the original items to a class by themselves and makes them incomparable to anything else. The real is the trump card of the museums. The more freewheeling flow of pictures, the more monitors and TV-screens that are put up wherever you turn, the more worthless copies, the more tokens are circulated, the larger is the hunger for real things. The museum is the very place where the flow of copies ends, the place where the neverending maelstrom of reproductions is stopped, in the museums there is peace, here the flicker and the noise and absent-minded clicking of the mouse ends, here the world begins. At a time where the monitor replaces reality, museums may satisfy the hunger for the real thing. The de-realisation of reality, the daily encounter with fleeting pictures of things has created a huge demand for meeting the things in themselves. Museums are a countermeasure against the monitors. The museums safeguard the spaciousness and the plasticity, the tangibly existing against the cold immateriality of cyberspace. The truth is concrete, not abstract. If the museums want it, they have a future. The museums are the owners of a marvellous raw material, which on the other hand gives no guarantee of success; it is merely the prerequisite for success – just as the best theat replay does no t guarantee a successful performance. The good exhibition makes it possible to rediscover direction and meaning in a world tortured by fear of the future. If the museums would trust themselves and open their eyes to the immense treasure of original objects that they have at their disposal and not let themselves be seduced by all the talk of the great narrative being lost and everything being hopeless, then they have a great time ahead of them. I for one am not worried. Thorkild Kjærgaard Nordborg Translated by Annette Lerche Trolle